Political Economy Analysis for Transboundary Water Resources Management in Africa : Practical Guidance - World Bank Group (World Bank, Washington, DC, 2017)
Fostering cooperation to optimize development outcomes in complex African river basins requires a nuanced understanding of context, especially the political and economic incentives facing local actors. Decisions related to water resources management are shaped by a range of considerations from traditional economic factors and physical constraints to political considerations such as the need to manage political support within a single state or to navigate complex international relationships with riparian countries. Exploring political economy realities can reveal capacities and systems that support pockets of effectiveness or have produced successful reforms in the past. It can also reveal the underlying logic behind seemingly irrational policy decisions or apparently dysfunctional institutional arrangements. This in turn provides the basis for thinking about how to work with, around, or gradually reshape existing systems to achieve developmental policy goals. Political Economy Analysis for Transboundary Water Resources Management in Africa introduces key concepts and variables for the transboundary water context. Furthermore, it provides practical advice to help water resource management specialists carry out strong, operationally relevant analysis that contributes to new ways of thinking and working, and ultimately to achieving better results. The note draws on the numerous frameworks that have been developed and the many lessons learned about how to design and implement politically sensitive programming. Importantly, while political economy assessments provide insights into the non-technical drivers of decision-making, they rely on a sound understanding of the technical bottlenecks that need to be resolved, as well as the economic and social costs and benefits of a given intervention.